Forward Vaccinology: CTL Targeting Based upon Physical Detection of HLA-Bound Peptides - Reinherz, Ellis L.; Keskin, Derin B.; Reinhold, Bruce (Frontiers in Immunology, 2014)
Vaccine-elicited cytotoxic T lymphocytes (CTL) recognizing conserved fragments of a pathogen's proteome could greatly impact infectious diseases and cancers. Enabling this potential are recent advances in mass spectrometry that identify specific target peptides among the myriad HLA-bound peptides on altered cells. Ultrasensitivity of these physical detection methods allows for the direct assessment of peptide presentation on small numbers of tissue-derived cells. In addition, concurrent advances in immunobiology suggest ways to induce CTLs with requisite functional avidity and tissue deployment. Elicitation of high avidity resident memory T cells through vaccination may shift the vaccinology paradigm both for preventive and therapeutic approaches to human disease control.